Assessement of crop loss in cowpea (Vigna unguiculata [L] Walp) caused by Sphaceloma sp., causal agent of scab disease - Mungo, C.M.; Emechebe, A.; Cardwell, K. (Elsevier, 1995)
IT 84S-2140 and IT 85F-1517 (cowpea varieties) susceptible to scab disease caused by Sphaceloma sp. were treated with severely infected cowpea plants in 1989 and 1990 field trials. Different levels of disease intensity were generated by treatment with benomyl using two different methods of application: varying the frequency of application from 4- to 35-day intervals resulted in grain losses ranging between 25–70% in 1989 and 35–50% in 1990. When the concentration of benomyl was varied at a 10-day interval, crop losses ranged between 10 and 71% in 1989 and 9–70% in 1990. Grain yield was significantly negatively correlated with leaf, stem, peduncle, flowering cushion and pod scab severities. The linear regression of grain yield on disease was computed using the critical point model. The results indicate that a weekly spray of benomyl at 0.5 kg/400 l−1 will prevent abscission of flowers, reduce heavy scabbing of young pods which in all interact to play an important role in crop loss due to cowpea scab. Cowpea scab can cause up to 71% crop loss in susceptible varieties if uncontrolled.